Breaking the Redox Homeostasis: an Albumin‐Based Multifunctional Nanoagent for GSH Depletion‐Assisted Chemo‐/Chemodynamic Combination Therapy. (26th March 2021) - Liang, Kaicheng; Sun, Haitao; Yang, Zebin; Yu, Huizhu; Shen, Jie; Wang, Xiaolin; Chen, Hangrong
Abstract: Redox homeostasis is vital for cell survival. Nowadays, developing novel nanoagents that can efficiently break the redox homeostasis, which includes improving the reactive oxygen species level while reducing the glutathione (GSH) level, has emerged as a promising but challenging strategy for tumor therapy. In this work, a novel albumin‐based multifunctional nanoagent is developed for GSH‐depletion assisted chemo‐/chemodynamic combination therapy. Briefly, CuO and MnOX are in situ co‐grown inside the albumin molecules through a facile biomineralization process, followed by the conjugation of Pt (IV) prodrug to obtain the final nanoagent. Thereinto, copper species can produce OH with optimal efficiency under weakly acidic conditions (pH = 6.5), while MnOX can react with GSH, leading to the GSH depletion, which reduces the formation of GSH‐Pt adducts and OH consumption, thus favoring a better chemotherapy and chemodynamic therapy effect, respectively. Significantly, both GSH depletion and OH generation contributes to the inhibited expression of GPX‐4, which further increases the oxidative stress. Moreover, during the reaction between MnOX and GSH or H2 O2, Mn 2+ ions are released for MR imaging while O2 is produced for hypoxia relief. It is believed that the proposed strategy can provide a new perspective on effective tumor therapy. Abstract : A novel albumin‐based multifunctional nanoagent is constructed through in situ co‐growth of CuO and MnOX inside albumin molecules followed by the conjugation of Pt (IV) prodrug. Optimal OH generation efficiency is achieved by copper species under tumor microenvironment while GSH depletion is achieved mainly by MnOX, which benefits chemotherapy and chemodynamic therapy effects.